Implementasi Multimedia Audiovisual dalam Pembelajaran Akidah Akhlak untuk Meningkatkan Prestasi Belajar Siswa di MTSN 2 Surakarta - Salsabilla Septiana Putri; Triono Ali Mustofa (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to determine the implementation of audiovisual multimedia in learning moral beliefs in MTs N 2 Surakarta, with the aim of improving student learning achievement. The method used is a qualitative case study, which involves direct observation in the classroom and interviews with teachers of moral beliefs. The results of the study showed that the use of audiovisual media, such as animation and video, significantly increased student engagement, comprehension, and material resistance. Despite obstacles such as time, technical, and unstable internet connections, supporting factors such as adequate technological infrastructure, teacher skills, and high student interest in learning contribute positively to learning effectiveness. This study concludes that multimedia can effectively improve students' academic performance in moral beliefs, making learning more concrete and accessible. Future prospects include improving technological infrastructure, teacher training and creating a conducive learning environment, as well as means for further research to explore, methods and other learning media.